2017
DOI: 10.1111/php.12743
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heterogeneity on the Ultrafast Photoisomerization Dynamics of Pfr in Cph1 Phytochrome

Abstract: Photoisomerization of a protein-bound chromophore is the basis of light sensing and signaling in many photoreceptors. Phytochrome photoreceptors can be photoconverted reversibly between the Pr and Pfr states through photoisomerization of the methine bridge between rings C and D. Ground-state heterogeneity of the chromophore has been reported for both Pr and Pfr. Here, we report ultrafast visible (Vis) pump-probe and femtosecond polarization-resolved Vis pump-infrared (IR) probe studies of the Pfr photoreaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 43 publications
(71 reference statements)
1
25
1
Order By: Relevance
“…Our earlier studies revealed that the Pr state is structurally heterogeneous in both oat phyA3 and Cph1, several carbons in/around the A -ring region, the C -ring propionate and several protein residues nearby showing at least two conformations associated with different hydrogen bonding networks ( Song et al, 2013 ). Heterogeneity in Pfr has also been described on the basis of resonance Raman and ultra-fast absorbance spectroscopy ( Kim et al, 2014 ; Velázquez Escobar et al, 2015 ; Stensitzki et al, 2017 ). In the present work, the N22 peak at ∼141 ppm in the 1D 15 N spectrum ( Figure 2B ) is asymmetrical and significantly broader than the other three, deconvolution revealing components at 140.7 and 142.1 ppm with an intensity ratio ∼0.7:0.3 ( Figure 2B ), perhaps implying heterogeneity at this point.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our earlier studies revealed that the Pr state is structurally heterogeneous in both oat phyA3 and Cph1, several carbons in/around the A -ring region, the C -ring propionate and several protein residues nearby showing at least two conformations associated with different hydrogen bonding networks ( Song et al, 2013 ). Heterogeneity in Pfr has also been described on the basis of resonance Raman and ultra-fast absorbance spectroscopy ( Kim et al, 2014 ; Velázquez Escobar et al, 2015 ; Stensitzki et al, 2017 ). In the present work, the N22 peak at ∼141 ppm in the 1D 15 N spectrum ( Figure 2B ) is asymmetrical and significantly broader than the other three, deconvolution revealing components at 140.7 and 142.1 ppm with an intensity ratio ∼0.7:0.3 ( Figure 2B ), perhaps implying heterogeneity at this point.…”
Section: Resultsmentioning
confidence: 99%
“…The observed 13 C and 15 N line-narrowing in Pfr results from greater structural homogeneity and reduced mobility of the surrounding protein relative to Pr in which the chromophore is loosely embedded in a soft pocket. Resonance Raman spectra of Xanthomonas BphP also imply increased dynamics in the Pr chromophore ( Otero et al, 2016 ), whereas other prokaryotic phytochromes showed greater Pfr chromophore heterogeneity ( Salewski et al, 2013 ; Kim et al, 2014 ; Velázquez Escobar et al, 2015 ; Stensitzki et al, 2017 ). Even if these effects also exist in plant phytochromes, we suspect that their dynamics would be too fast and/or the movements too subtle to be detected by MAS NMR.…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous findings and the small kinetic isotope effect associated with this step, it is likely that this feature is due to the deprotonation of one of the propionic side chains. The disappearance of the positive feature at trueν˜ =1717 cm −1 is assigned to the C=O bond of ring D, in accordance with previous studies of similar systems . The λ =625 nm absorbing intermediate described by EADS4 is then converted into an intermediate with an absorption maximum at λ =610 nm (EADS5) with a lifetime of 275 μs (482 μs in D 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…For this purpose, classical MD simulations were performed by several groups [25,26,27,28]. In addition, Mroginski and coworkers also employed QM/MM simulations [29,30,31] and some recent publications based on this approach can be found in references [32,33,34,35,36,37]. Recently a QM/MM approach was also applied to investigate the covalent binding of the biliverdin (BV) chromophore to phytochrome domains [38] in the NIR FP miRFP670, which was also investigated experimentally [39,40,41].…”
Section: Introductionmentioning
confidence: 99%